2016
DOI: 10.1021/acs.jpcc.6b07701
|View full text |Cite
|
Sign up to set email alerts
|

The Mixing Behavior of Alkanes Adsorbed on Hexagonal Boron Nitride

Abstract: In this work, we report the mixing behavior of a series of normal alkanes adsorbed on the surface of hexagonal boron nitride (h-BN) using X-ray powder diffraction. We have investigated a range of simple binary mixtures which are indicative of a rich phase behavior with examples of complete mixing, partial mixing, and phase separation. On graphite surfaces, the mixing behavior is strongly influenced by the structure of the pure components; the odd−even effect seen in the pure structures, which favors either a "… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Furthermore, hBN has been used successfully as a dielectric in organic transistors. 30,31 However, the adsorption of alkanes on hBN has so far been studied only using diffraction techniques, 32,33 with no direct determination of their real-space arrangement and potential to control supramolecular organization.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, hBN has been used successfully as a dielectric in organic transistors. 30,31 However, the adsorption of alkanes on hBN has so far been studied only using diffraction techniques, 32,33 with no direct determination of their real-space arrangement and potential to control supramolecular organization.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It has also been shown that hBN, both in the form of monolayers (MLs) grown on metals and thicker exfoliated flakes, can support the formation of two-dimensional supramolecular assemblies. Furthermore, hBN has been used successfully as a dielectric in organic transistors. , However, the adsorption of alkanes on hBN has so far been studied only using diffraction techniques, , with no direct determination of their real-space arrangement and potential to control supramolecular organization.…”
Section: Introductionmentioning
confidence: 99%
“…In the US, nearly half of the rivers and streams and more than one-third of the lakes are polluted according to the data disclosed by United States Environmental Protection Agency. , China’s water pollution problems are even more serious and widespread: according to the data presented by the Joint Monitoring Program for Water Supply and Sanitation of WHO, about 36% of the rural population in China relies on tainted water . Although water pollution can be caused in a number of ways, chemicals and microorganisms from industrial waste discharge and city sewage are the most common causes. Short-chain alkyl derivatives, such as short linear halides, alcohols, amines, ethers, aldehydes, ketones, esters, carboxylic acids, ammonium salts, and sulfonic acids, are widely used in chemical and pharmaceutical industries as well as household product industry as reagents, solvents, additives, or surfactants. As a result, these kinds of chemicals are often found in the polluted water caused by industrial waste discharge and sanitary wastewater. In water purification, adsorbents such as zeolite , activated carbon, ordered mesoporous silica, and microporous polymer have been extensively used to remove pollutants from water.…”
Section: Introductionmentioning
confidence: 99%